Dynamic organization of the actin cytoskeleton during meiosis and spore formation in budding yeast - Taxis, Christof; Maeder, Céline; Reber, Simone B.; Miura, Kota; Greger, Klaus; Stelzer, Ernst H. K.; Knop, Michael (Traffic, 2006)
During sporulation in Saccharomyces cerevisiae, the four daughter cells (spores) are formed inside the boundaries of the mother cell. Here, we investigated the dynamics of spore assembly and the actin cytoskeleton during this process, as well as the requirements for filamentous actin during the different steps of spore formation. We found no evidence for a polarized actin cytoskeleton during sporulation. Instead, a highly dynamic network of non-polarized actin cables is present underneath the plasma membrane of the mother cell. We found that a fraction of prospore membrane (PSM) precursors are transported along the actin cables. The velocity of PSM precursors is diminished if Myo2p or Tpm1/2p function is impaired. Filamentous actin is not essential for meiotic progression, for shaping of the PSMs or for post-meiotic cytokinesis. However, actin is essential for spore wall formation. This requires the function of the Arp2/3p complex and involves large carbohydrate-rich compartments, which may be chitosome analogous structures.
Gesehen am 16.08.2017